Hereditary Angioedema Type 1 and 2 in Finland: Incidence, Prevalence, and Preceding Diagnoses - Andreas Sandberg; Mariann Lassenius; Ville Vihervaara; Iiro Toppila; Laura Huilaja (Medical Journals Sweden, 2024)
Abstract is missing (Short communication)